A novel approach to a fully inkjet printed SnO2-based gas sensor on a flexible foil. Issue 39 (30th September 2019) - Kassem, Omar; Saadaoui, Mohamed; Rieu, Mathilde; Viricelle, Jean-Paul
Abstract : In recent years, printed and flexible gas sensors have quickly emerged as an innovative area of great interest because of their lightness and low cost. Abstract : In recent years, printed and flexible gas sensors have quickly emerged as an innovative area of great interest because of their lightness and low cost. These flexible sensors can be easily integrated into autonomous systems for many applications such as smart food packaging and premature disease detection. In this paper, a novel approach was applied to manufacture a fully inkjet-printed gas sensor on a flexible polymeric foil. A platinum heater and gold electrodes were printed on the top side of the substrate, separated by a thin insulating layer of printed polyimide. An aqueous sol–gel process was adopted to synthesize nanosized SnO2 -based sol that guarantees crystallization at 350 °C, which is entirely consistent with the polyimide foil. Then, the sol was transformed into a stable ink and inkjet printed over the gold electrodes. The printability of different inks was optimized to ensure flawless ejection of droplets, and the complex physico-chemical interactions between the inks and different interfaces were controlled to get well-defined patterns with high resolution. Finally, electrical measurements of the printed sensor were performed to characterize the response and sensitivity to different concentrations of ethanol, ammonia and carbon monoxide gases, at a working temperature of 300 °C, in dry and wet air.